(untitled) (Global Journal of Medical Research, 2023)
Modern dynamic radiotherapy techniques require more precision and need routine checking However presently available methods for Dosimetric Leaf Gap DLG and MLC transmission factor are highly time-consuming so they are not feasible for busy radiotherapy centers This analytical and observational study tried to determine the most straightforward way of simultaneously determining the transmission and DLG in the shortest time We measured all data at 5cm depth using a Varian VitalBeam LINAC newly installed at TMSS Cancer Center Bogura Bangladesh We used three significant pieces of equipment in our experiment an integrated Electronics Portal Imaging Device EPID a solid water phantom and a farmer-type ion chamber Model IBA FC65-P The Eclipse TPS was also used to make the QA plan and to analyze the images